Optimization and Characterization of Liquid Smoke Produced by Terminalia catappa Wood Pyrolysis and its In Vitro Antifungal Activity - Oramahi, Hasan Ashari; Maurisa, Tirsa; Nurhaida; Darwati, Herlina; Rifanjani, Slamet (Science and Technology Indonesia, 2024)
This research utilized response surface methodology (RSM) to explore how the yield of liquid smoke obtained from ketapang wood (Terminalia catappa) is influenced by the size of wood particles and the temperature of pyrolysis. Gas chromatography-mass spectrometry (GC-MS) was used to characterize the liquid smoke. To assess liquid smoke’s antifungal effects, a petri dish bioassay was conducted using 1.0-4.0% (v/v) concentrations against Schizophyllum commune. RSM was applied to optimize vinegar from T. catappa by varying the wood particle size and the pyrolysis temperature. The optimal yield, 24.67%, was obtained with a 3.22 mm particle size and a 425°C pyrolysis temperature. The liquid smoke produced at 400-450°C completely inhibited of S. commune growth at 2.0-4.0%. The primary components of the liquid smoke at 400°C were 2-methoxy- phenol (24.85%), creosol (8.39%), 4-ethyl-2-methoxy- phenol (7.21%), 2-5-methyl-furancarboxaldehyde (4.55%), and 4-ethyl-2-methoxy-phenol (3.74%). The primary components at 425°C were 2-methoxy-phenol (25.60%), creosol (15.15%), 5-methyl-2 furancarboxaldehyde (12.75%), and 2,6-dimethoxy-phenol (9.31%). At 450°C, the main components were 2-methoxy-phenol (25.26%), 4-ethyl-2-methoxy-phenol (8.46%), creosol (8.40%), 5-methyl-2-furancarboxaldehyde (4.02%), and 4-ethyl-2-methoxy-phenol (3.98%).